An Investigation of Differences in Residents' Perceptions on the Kumbalanghi Village in Ernakulam, Kerala: Tourism Impacts and Demographic Variables - P.C. Radhika and Dr. Johney Johnson
The resident community of destination is one of the major stakeholders of tourism and their support is important for the sustainable development of the destination. It is very important to understand the different factors which affect their support. Most of the literature shows the resident’s perceptions of tourism impacts are the major predictor of their support and the present study was conducted with the objective of whether the demographic variables such as age, marital status, sex and educational qualification have got any effect on residents’ perceptions of various tourism development impacts. The study was conducted in Kumbalanghi village in Ernakulam district. The study found that age and marital status are predictor of on residents’ perceptions of various tourism development impacts and the study didn’t finds any significance for gender and educational qualification in predicting the residents’ attitudes towards the perceived impacts of tourism.